Pawsitive Solutions: an Overview of Prison Dog Programs in Australia - Humby, Lauren (The prison journal, 2018)
A survey of animal welfare agencies and corrections departments across Australia was conducted to compile a nationwide profile of prison dog programs, wherein inmates train dogs while learning skills to assist their rehabilitation. Most programs operating in 23 prisons in six Australian states were a community service design administered by animal welfare organizations. Inmates benefit through opportunities to train the dogs, give back to society, gain a sense of responsibility, improve self-confidence and social skills, and acquire vocational qualifications to improve job opportunities postrelease. Barriers identified included insufficient funding, limited training opportunities for the dogs, and some staff resistance.